Chinese Medicinal Leech: Ethnopharmacology, Phytochemistry, and Pharmacological Activities - Han Dong; Jixiang Ren; Jingjing Wang; Li-Shuai Ding; Zhao Jian-jun; Songyan Liu; Hui‐Min Gao (2016)
Hirudo (Shuizhi in Chinese) is an important Chinese medicine, which possesses many therapeutic properties for the treatment of the cerebral hemorrhage and other thrombosis‐related diseases. The phytochemical investigation gave more than 51 compounds including pteridines, phosphatidylcholines, glycosphingolipids, and sterols, as well as some bioactive peptides from the Shuizhi derived from three animal species recorded in the current Chinese Pharmacopoeia. The pharmacological studies on the Shuizhi have revealed various activities such as anticoagulation, antithrombosis, antiatherosclerosis, antiplatelet aggregation, antitumor and anti‐inflammatory as well as hemorheology improvement, and protective effects against cerebral ischemia‐reperfusion injury. However, some important issues based on the traditional uses of Shuizhi are still not clear. The aim of the present review is to provide comprehensive knowledge on the ethnopharmacology, phytochemistry, and pharmacological activities of Shuizhi. It will provide a potential guidance in exploring main active compounds of Shuizhi and interpreting the action mechanism for the further research.